2018
DOI: 10.1002/chir.22817
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical structure‐property relations in cyclo[18]carbon and its in silico hydrogenation products

Abstract: The anisotropy of the optical activity of cyclo[18]carbon (C ), fully hydrogenated C (C H ), and 26 hydrogenated compounds of intermediate composition, C H , n = 1,2…17, were computed. These compounds were selected because they resemble loops of wire. The maximum gyration for acetylenic and cumulenic subgroups of compounds was linearly proportional to the product of the geometric area over which the charge can circulate, multiplied by the largest separation between carbon atoms on opposing sides of the loops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Numerous electronic structure calculations of cyclo [18]carbon molecule have been carried out at the different levels of theory including the HF, 18,20 SCF, [21][22][23] MCSCF, 24 MP2, 21,22 DFT, 19,21,[25][26][27][28][29][30][31][32] quantum Monte Carlo (QMC) 24 and CCSD 23,29 levels. Surprisingly, only the HF, QMC and CCSD methods yield the polyyne structure that experimentally has been observed in high-resolution atomic force microscopy (AFM) measurements of cyclo [18]carbon adsorbed on bilayer NaCl on Cu(111) surface at the temperature of 5 K. 16 Most of the common DFT functionals 19,21,[25][26][27][28][29][30][31][32] (B3LYP, BLYP, PBE0, etc.) as well as MP2 calculations 21 yield the nonbond-length alternating cumulene structure of cyclo [18]carbon.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous electronic structure calculations of cyclo [18]carbon molecule have been carried out at the different levels of theory including the HF, 18,20 SCF, [21][22][23] MCSCF, 24 MP2, 21,22 DFT, 19,21,[25][26][27][28][29][30][31][32] quantum Monte Carlo (QMC) 24 and CCSD 23,29 levels. Surprisingly, only the HF, QMC and CCSD methods yield the polyyne structure that experimentally has been observed in high-resolution atomic force microscopy (AFM) measurements of cyclo [18]carbon adsorbed on bilayer NaCl on Cu(111) surface at the temperature of 5 K. 16 Most of the common DFT functionals 19,21,[25][26][27][28][29][30][31][32] (B3LYP, BLYP, PBE0, etc.) as well as MP2 calculations 21 yield the nonbond-length alternating cumulene structure of cyclo [18]carbon.…”
mentioning
confidence: 99%
“…Numerous electronic structure calculations of the cyclo[18]­carbon molecule have been carried out at the different levels of theory, including the HF, , SCF, MCSCF, MP2, , DFT, ,, quantum Monte Carlo (QMC), and CCSD , levels. Surprisingly, only the HF, QMC, and CCSD methods yield the polyyne structure that experimentally has been observed in high-resolution atomic force microscopy (AFM) measurements of cyclo[18]carbon adsorbed on bilayer NaCl on a Cu(111) surface at a temperature of 5 K .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This work showed that the large [α] ω of (1 S ,4 S )-norbornenone is due to electron delocalization between the CO and CC chromophores . Kahr and co-workers extended the analysis of optical activity to include nonchiral molecules through a simple and effective Hückel theory decomposition. , Wiberg examined the effect on [α] ω of the rotation of the torsional angle of terminally substituted 1,4-pentadiene (CC to CX interactions, where X = C, O, NH, and S) and found a dependence on the electronegativity of X. , We have also introduced a method of decomposing [α] ω in terms of transition electric and magnetic dipole contributions, called the S̃ k method (discussed in Section ). , We showed that a limited number of orbital transitions can be used to describe [α] ω for molecules with strong chromophoric groups and that changes in [α] ω due to conformational flexibility are dominated by a small number of transitions, thus simplifying the interpretation of the structure–property relationship.…”
Section: Introductionmentioning
confidence: 99%
“…18 Kahr and co-workers extended the analysis of optical activity to include nonchiral molecules through a simple and effective Huckel theory decomposition. 19,20 Wiberg examined the effect on [α] ω of the rotation of the torsional angle of terminally substituted 1,4-pentadiene (CC to CX interactions, where X = C, O, NH, and S) and found a dependence on the electronegativity of X. 21,22 We have also introduced a method of decomposing [α] ω in terms of transition electric and magnetic dipole contributions, called the S ̃k method (discussed in Section 2).…”
Section: Introductionmentioning
confidence: 99%